Back Cover: General Formation of Complex Tubular Nanostructures of Metal Oxides for the Oxygen Reduction Reaction and Lithium‐Ion Batteries (Angew. Chem. Int. Ed. 33/2013). Issue 33 (26th July 2013) - Zhang, Genqiang; Xia, Bao Yu; Xiao, Chong; Yu, Le; Wang, Xin; Xie, Yi; Lou, Xiong Wen (David)
<x xml:space="preserve">Abstract</x> Complex hollow tube‐in‐tube nanostructures have been fabricated for many metal oxides through a general strategy, as described by X. W. Lou, Y. Xie, et al. in their Communication on page 8643 ff. The method involves two simple steps: coating carbon nanofibers with a layer of metal glycolate and subsequent calcination in air. The unique complex tubular metal oxide structures are promising electrocatalysts for the oxygen reduction reaction and electrode materials for lithium ion batteries.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>